Multi‐agent evolutionary game of process safety culture in Chinese chemical industry based on system dynamics. Issue 2 (5th November 2021) - Liu, Tong; Zhang, Ming‐guang; Song, Jian; Zhao, Yao
Abstract: In the process of safety culture construction in Chinese chemical industry, various interests and relationships of stakeholders involved are complicated, which hinders the process safety culture in chemical industry from being implemented practically. Thus, evolutionary game theory was used to draw the relationships between the stakeholders, including China chemical safety supervision department, chemical plants, and chemical plant workers. A system dynamics model was built to explore the dynamic relationships of process safety culture in Chinese chemical industry, and study the dynamic stability of stakeholders. The simulation results show that the strategy selections of China chemical safety supervision department, chemical plants, and chemical plant workers could reach a stable condition, which indicates that the evolutionary stable strategy exist in the current dynamic interaction among the three agents. Furthermore, a sensitivity analysis between state variables and several auxiliary variables were accomplished to reveal the internal relationships. The proposed new method of applying evolutionary game to process safety culture offers a solution to optimize safety culture construction.